New or poorly known Neocomitidae (Ammonitina, Ammonoida) from the lower Hauterivian sedimentary series of the Jura platform and the Vocontian trough (France and Switzerland) - Antoine Pictet; Luc Georges Bulot (Swiss Journal of Palaeontology)
Abstract The Hauterivian type region and more widely the Jura mountains were investigated for their ammonites of the family Neocomitidae. Three rare lower Hauterivian genera are described here: (i) a more detailed description of Haroella charcensis Bulot, Pictet, Frau & Bryers, 2024 is given, which was identified in historical collections of ammonites from the Jura mountains, originating from a phosphatic conglomerate dating from the local Leopoldia buxtorfi Horizon and making it the oldest representative of the genus; (ii) Lyticoceras subhystricoides (Kilian & Reboul, 1915) from the Eclépens quarry is currently being revised as Theodorites cf. theodori Baraboshkin and Mikhailova, 2006; (iii) the new genus Jurienella is introduced for “Breistrofferella” peyroulensis Atrops, Autran & Reboulet 1996, previously known only to a few Provençal sections, in SE France. The stratigraphic position of the Jura specimens raises questions about the age of this taxon, as well as the phyletic link between the genera Bresitrofferella Thieuloy, 1971 and Acanthodiscus Uhlig, 1905. The Haroella-Theodorites lineage is presently considered to be separate from the Lyticoceras-Cruasiceras lineage. The Haroella-Theodorites lineage seems to originate from, or to be closely allied to the late Valanginian species Distoloceras hystrix (Phillips, 1829) sensu Neumayr & Uhlig, genotype of Distoloceras.